2020
DOI: 10.3390/metabo10090362
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metabolites and the Risk of Lung Cancer: A Systematic Literature Review and Meta-Analysis of Observational Studies

Abstract: Globally, lung cancer is the most prevalent cancer type. However, screening and early detection is challenging. Previous studies have identified metabolites as promising lung cancer biomarkers. This systematic literature review and meta-analysis aimed to identify metabolites associated with lung cancer risk in observational studies. The literature search was performed in PubMed and EMBASE databases, up to 31 December 2019, for observational studies on the association between metabolites and lung cancer risk. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 169 publications
4
16
0
Order By: Relevance
“…It is well known this metabolite is involved in various important activities in cancer cells, such as nucleotide biosynthesis via the one-carbon metabolism pathway and protein synthesis. Relating specifically to lung cancer, several published studies suggested that plasma methionine concentration is decreased [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known this metabolite is involved in various important activities in cancer cells, such as nucleotide biosynthesis via the one-carbon metabolism pathway and protein synthesis. Relating specifically to lung cancer, several published studies suggested that plasma methionine concentration is decreased [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…NANA is involved in the formation of glycans, which plays several important roles in cells, namely in proteins synthesis, cell signaling and adhesion. Increased NANA levels may be a result of increased turnover and shedding of tumor cells, which in turn results in the release of glycans into the serum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the package, we selected a metabolomics meta-analysis with data disclosed ( Lee et al , 2020 ) which describes the association of metabolites with lung cancer risk. We could only use the information of amino acids concentration disclosed in six studies to compare both methodologies, as it was the only fully available ( Supplementary Table S2 ).…”
Section: Validationmentioning
confidence: 99%
“…Typical protocols for meta-analysis only consider one metric to conduct the analysis, whether statistical significance or relative change. They require raw data [Metaboanalyst’ ( Chong et al , 2018 )] or statistics parameters like standard error, standard deviation or variance [R package ‘meta’ ( Balduzzi et al , 2019 )], rarely disclosed in metabolomics studies ( Lee et al , 2020 ; Tofte et al , 2020 ). This causes that in some cases about half of the studies on systematic reviews are not suitable to be included in the meta-analysis ( Guasch-Ferré et al , 2016 ; Pang et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another candidate for the biomarker of lung cancer is circulating free DNA (cfDNA) [ 14 ] and circulating tumor cells (CTC) [ 15 ]. More recently, serum metabolites and lipids have emerged as another class of potential biomarkers in lung cancer [ 16 , 17 ]. Several other review papers could be suggested that cover this well-researched field [ 11 , 12 , 13 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%